Faktor-Faktor yang Berhubungan dengan Kepatuhan Perawat Terhadap Risiko Jatuh di Ruang Nilam RSUD Dr. H. Moch. Ansari Saleh Banjarmasin - Sari, Yunita; Ariadi, Herman; Sukarlan, Sukarlan; Amaliah, Noor (Pustaka Galeri Mandiri, 2026)
Patient falls are a patient safety issue that can cause serious injury or death; therefore, nurses’ adherence to the Standard Operating Procedure (SOP) for fall-risk prevention must be maintained consistently. To analyze the association of age, workload, and nurses’ attitudes with nurses’ compliance with fall-risk prevention in Nilam Wards 1 2 at Dr. H. Moch. Ansari Saleh General Hospital, Banjarmasin. A quantitative analytic cross-sectional study involving 41 nurses (total sampling) conducted on 13–16 January 2026. Data were collected using a biodata sheet and modified questionnaires on compliance (Putrina, 2019), workload (Subagya, 2016), and attitude (Fajrin, 2024) with validity reliability testing. Univariate (frequency percentage) and bivariate (Spearman) analyses were performed. Most respondents were adults (82.9%), reported light workload (92.7%), had positive attitudes (90.2%), and were compliant with the fall-prevention SOP (87.8%). Spearman test showed no significant association between age and compliance (p=0.291; r=0.169), while workload was significantly associated with compliance but with a weak correlation (p=0.040; r=0.317), and attitude was significantly associated with compliance but with a weak correlation (p=0.027; r=0.225). Nurses’ compliance is associated with work conditions (workload) and individual factors (attitude); thus, sustaining compliance should focus on proactive SOP integration into daily workflow, audit–feedback, and strengthening a patient-safety culture not only after fall incidents.